Evolution of the body fat percentage of a professional soccer team over three seasons. (Spanish First Division La Liga) - Del Valle Pascual, F.; Gomez Vera, G. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Nowadays, Soccer is the sport which has the most practitioners, besides a lot of supporters. Professional football clubs, which play in the biggest leagues and championships, count on an increasingly high budget. This has led to soccer players receiving the best medical care, aiming to maintain an appropriate health and performance status, among other aspects. To provide these services, it is necessary that doctors, fitness coaches, rehab fitness coaches, physiotherapists, psychologists and nutritionists work closely together. The multidisciplinary approach of all these specialists can bring the players towards success. At the beginning of the season, one of the factors to monitor is the nutritional assessment, where the body composition measure is. The body fat percentage is one of the factors to consider, since the references values in elite soccer players have proved a better performance and lower injury risks. For this reason, it is vitally important to know this percentage, in order to provide an ideal competition weight to the players. It will contribute to improve the nutritional strategies which will help them to enhance their performance. The aim of this study was to describe the evolution of the body fat percentage of a professional soccer team, over three seasons. Twenty five players from several nationalities and from the same team were followed for three seasons. Their ages, body weight and height were 24±4, 28±2 and 29±3 years old, 75±7, 77±5 and 76±6 kg, and 179±6, 178±6, 179±6 cm in the season 13/14, 14/15 and 15/16 respectively. We analyzed the triceps, subscapular, supraspinale and abdominal skinfolds following the guidelines of The International Society for the Advancement of Kinanthropometry (ISAK), by accredited researchers, calculating the body fat percentage using the Faulkner formula. The highest body fat percentage was found in July, at the beginning of the pre-season (12±2%, 12±1% and 11±1% in the season 13/14, 14/15 and 15/16 respectively). Comparisons between measurements were performed by analysis of variance (ANOVA), for checking the level of significance of the mean fat percentage of each of the monthly measurements per season. No differences (p> 0.05) between the means monthly measurements per season were found. Despite the absence of significant differences, we concluded that the body fat percentage can change due to different factors, such as the ups and downs of the team in the championships or injuries. In the pre-season, players come with the highest levels of body fat percentage. Therefore, dietary monitoring of the players must be the key to improving their performance during the season.